The Effect of Enterococcus faecalis Bacteria on Expired Cosmetics: A Literature Review - Aghni, Hasna Tazkia; Putri, Nadya Armelisa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The use of cosmetics has become a daily necessity for modern society, both for men and women. However, cosmetic products that have passed their expiration date have the potential to become a medium for the growth of pathogenic microorganisms, one of which is Enterococcus faecalis. This gram-positive bacterium is capable of forming biofilms on the surface of cosmetics, thereby increasing its resistance to the host's immune system and various antibiotics. Contamination of expired cosmetics with Enterococcus faecalis can cause mild symptoms such as skin irritation, acne, and itching, as well as severe complications like meningitis and septicemia. Additionally, the antibiotic resistance possessed by this bacterium exacerbates clinical risks and complicates treatment. Therefore, understanding the dangers of using expired cosmetics is crucial for raising public awareness. Prevention can be achieved by paying attention to product shelf life, maintaining applicator hygiene, and avoiding the use of cosmetics that have passed their expiration date.